E = ( x − y ) ( x − z ) x 2 + ( y − x ) ( y − z ) y 2 + ( z − x ) ( z − y ) z 2
Let x = 1 0 0 8 , y = 2 0 1 6 , z = 4 0 3 2 . Find the exact value of E .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Lol.. z=4x and not 3x... :-)
Log in to reply
Hahah...z=3x..luckily works.Lol...fixed. Thanks! :)
Good noticing! I didn't intend for that, I intended for the usage of cyclic polynomial properties but nonetheless nice solution.
Let Ξ ( x , y , z ) = ( x − y ) ( y − z ) ( z − x ) ξ = − x 2 ( y − z ) − y 2 ( z − x ) − z 2 ( x − y ) .
RHS is order 3. Hence ξ = c , a constant. X i ( 0 , 1 , 2 ) = 2 ξ = 0 − 2 + 4 = 2 .
ξ ( x , y , z ) = 1 as long as x , y , z are distinct.
I used ξ because I wasn't sure how to get a curly e... and the question is easier with the values provided as 4 x = 2 y = z . Could throw people off it was 1 0 0 8 , 2 0 1 5 , 4 0 3 1 for example.
Problem Loading...
Note Loading...
Set Loading...
Notice that: y = 2 x and z = 4 x .
⇒ ( x − y ) ( x − z ) x 2 + ( y − x ) ( y − z ) y 2 + ( z − x ) ( z − y ) z 2
⟹ ( − x ) ( − 3 x ) x 2 + x ( − 2 x ) 4 x 2 + 3 x ( 2 x ) 1 6 x 2
⟹ 3 x 2 x 2 + − 2 x 2 4 x 2 + 6 x 2 1 6 x 2
⟹ 3 1 − 2 + 3 8 = 1